Advancements in strategies for overcoming the blood–brain barrier to deliver brain-targeted drugs - Qu, Zhichuang; Luo, Juan; Li, Zheng; Yang, Rong; Zhao, Jiaxi; Chen, Xin; Yu, Sixun; Shu, Haifeng (Frontiers in Aging Neuroscience, 2024)
The blood-brain barrier is known to consist of a variety of cells and complex intercellular junctions that protect the vulnerable brain from neurotoxic compounds; however, it also complicates the pharmacological treatment of central nervous system disorders as most drugs are unable to penetrate the blood-brain barrier on the basis of their own structural properties. This dramatically diminished the therapeutic effect of the drug and compromised its biosafety. In response, a number of drugs are often delivered to brain lesions in invasive ways that bypass the obstruction of the bloodbrain barrier, such as subdural administration, intrathecal administration, and convection-enhanced delivery. Nevertheless, these intrusive strategies introduce the risk of brain injury, limiting their clinical application. In recent years, the intensive development of nanomaterials science and the interdisciplinary convergence of medical engineering have brought light to the penetration of the blood-brain barrier for braintargeted drugs. In this paper, we extensively discuss the limitations of the blood-brain barrier on drug delivery and non-invasive brain-targeted strategies such as nanomedicine and blood-brain barrier disruption. In the meantime, we analyze their strengths and limitations and provide outlooks on the further development of braintargeted drug delivery systems.